A study of behavior of dielectrics subject to weak electric fields - Göktuna, Erol. (Thesis (M.S.)- Robert College. Faculty of Graduate School of Engineering, 1969., 1969)
The aim of this report is to investigate dielectric behavior at weak electric field. The behavior of permittivity, a defining property of dielectric materials, at weak fields is mostly discussed. The theoretical approach implies that the permittivity is not influenced by the field intensity at relatively weak electric fields. However, the external disturbances such as frequency, temperature, and humidity, play an important role in determining the permittivity. The temperature and frequency dependence of dielectric materials are also considered in connection with the electric field. The behavior of six different dielectric samples at relatively weak electric fields are investigated. These samples are.being used in Electro-Odqcell, an objective odor measuring instrument, on which a research work is going on at Robert College Research Center, under the supervision of Prof. Dr. Necmi Tanyolaç.
Keywords: Dielectrics.; Electrical engineering.; Electromagnetic fields.; Electric fields.